Virological response to a triple nucleoside/nucleotide analogue regimen over 48 weeks in HIV-1-infected adults in Africa. - DART Virology Group and Trial Team (2006)
OBJECTIVES: To evaluate virologic response up to 48 weeks, and emergence of HIV-1 resistance mutations at 24 weeks, in therapy-naive adults initiating zidovudine/lamivudine/tenofovir DF. DESIGN: : A cohort within the DART trial. METHODS: Plasma HIV-1 RNA was assayed in 300 adults with baseline CD4 cell count < 200 cells/mul from sites in Uganda and Zimbabwe using the Roche Amplicor assay v1.5. Samples with HIV-1 RNA > 1000 copies/ml at 24 weeks were sequenced in the pol region. RESULTS: Median baseline CD4 cell count was 101 cells/mul and HIV-1 RNA 279,910 copies/ml (mean, 5.4 log10). At 48 weeks, 61% (165/272) had HIV-1 RNA < 50 and 72% (196/272) < 400 copies/ml, compared with 59% (167/281) and 79% (221/281) at 24 weeks. At 24 and 48 weeks, 15 and 24% respectively had HIV-1 RNA > 1000 copies/ml (6 and 17% > 10 000 copies/ml), and mean CD4 cell count increases were 103 and 127 cells/mul, respectively. Higher baseline CD4 cell count was the most important predictor of virological suppression at 48 weeks, with little effect of baseline viral load. Eighteen of 20 genotypes from week 24 samples with HIV-1 RNA > 1000 copies/ml showed key resistance mutations in reverse transcriptase. Fourteen had M184V [10 with one to four additional nucleoside analogue mutations (NAMs)]; one had three NAMs only; and the remaining three had K65R. One participant with M184V had major non-nucleoside reverse transcriptase inhibitor-associated mutations, despite no disclosed treatment with this class. CONCLUSION: Zidovudine/lamivudine/tenofovir has good virological efficacy in advanced HIV disease. In this population, who were infected with HIV-1 subtypes A, C or D, M184V with or without NAMs was the most common route to resistance, whereas K65R was identified less often.